Enhanced Temperature Stability of High Energy Density Ferroelectric Polymer Blends: The Spatial Confinement Effect. Issue 21 (26th September 2019) - Liu, Yongbin; Gao, Jinghui; Wang, Yan; Zhou, Jun; Cao, Liang; He, Zhixin; Zhang, Yang; Tang, Chao; Zhong, Lisheng
Abstract: Thermal stability of polymer structure is a key to achieve stable energy density at elevated temperature for ferroelectric‐polymer‐based capacitors. Here, a poly (vinylidene fluoride) / polymethyl methacrylate (PMMA) blend with a stabilized spherulite structure displaying steady energy density around 7.8–9.8 J cm −3 across the temperature range up to 70 °C is reported, which outperforms most neat ferroelectric polymers at elevated temperature. The microstructure of the blend observed by atomic force microscopy exhibits an alternating lamellar structure (crystalline/mixed amorphous layers) within spherulites, which might be rationalized by PMMA being gradually expelled from the spherulite and finally staying between PVDF lamellae during crystallization. The structure with rigid amorphous layers can induce a spatial confinement effect of chain motion and structural change under thermal stress, which is evidenced by temperature‐insensitive long period in small‐angle X‐ray scattering measurements. The enhanced thermal stability of energy storage can be attributed to the constraint on free volume and carrier transportation caused by the spatial confinement. Our findings provide a strategy to attain temperature‐stable high‐energy‐density ferroelectric polymers for energy storage capacitors. Abstract : A blending strategy is proposed to stabilize energy storage performance over a wide temperature range in ferroelectric polymers. Temperature stability is caused by spatial confinement effect in alternating lamellar structure. High energy density and associated dielectric properties at elevated temperature is superior to other neat ferroelectric polymers.